2018
DOI: 10.1108/joe-10-2017-0052
|View full text |Cite
|
Sign up to set email alerts
|

Of being a container through role definitions

Abstract: Purpose The purpose of this paper is to reflect critically on the roles that women leaders in higher education institutions (HEIs) take on. Therefore, a systems psychodynamic view is used from a theoretical stance, while an autoethnographical methodology is applied to provide an in-depth emic view of, and reflections on, women leaders’ roles in the described context. Design/methodology/approach The study draws on the authors’ personal and organisational autoethnographical experiences as women leaders in HEIs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Women also indicated that perseverance, focusing on priorities, consulting widely and seeking support were critical in assisting them to succeed in their leadership positions. According to Mayer and May (2018), women leaders often experience thoughts and feelings of exclusion, marginalisation, voicelessness and a lack of authority.…”
Section: Obstacles Faced By Women Who Wish To Advance To Leadership Positionsmentioning
confidence: 99%
“…Women also indicated that perseverance, focusing on priorities, consulting widely and seeking support were critical in assisting them to succeed in their leadership positions. According to Mayer and May (2018), women leaders often experience thoughts and feelings of exclusion, marginalisation, voicelessness and a lack of authority.…”
Section: Obstacles Faced By Women Who Wish To Advance To Leadership Positionsmentioning
confidence: 99%